GUIELINES FOR TESTING OF ENGLISH COVERSATION - Issam Al-Kateb; John Pattison (آداب الرافدين, 1979)
These guidelines are intended to assist instructors teaching conversation to Iraqi students. They are related to the understanding and production of the language of ordinary speech rather than to theoretical phonetics, although some aspects of practical phonetics form parts of the testing. The areas suggested for testing are as follows: a. Comprehension b. Fluency c. Correctness d. Pronunciation